Analisis Variasi Rekonstruksi Increment Overlapping terhadap Informasi Citra Anatomi pada Pemeriksaan MSCT Nasofaring dengan Klinis Karsinoma - Jeffri Ardiyanto; Darmini Darmini; Widiya Purnama Sari (Poltekkes Kemenkes Semarang, 2017)
Background: In Nasopharyngeal MSCT examination, the radiologist wants optimal image in order to evaluate the characteristics of the tumor, bone destruction due to a tumor, the extent of tumor invasion and the detection of regional metastases that serve as guidelines in determining the clinical stage in patients with nasopharyngeal carcinoma. So setting the scan parameters rekostruksi increments during the process multiplanar reconstruction (MPR) image on Nasopharyngeal MSC T will produce optimal images for diagnosis enforcement. Overlapping reconstruction increment is the distance between the image that has been reconstructed on the data volume that is made smaller than the size of the slice thickness is used. Selection of the reconstruction value increment overlapping usage right has an advantage in generating image anatomical information better for image noise becomes lower and accurate for diagnosing small structures, especially of hidden nasopharynx anatomy and difficult to detect. The purpose of this study was to determine the influence variation reconstruction increment overlapping to the anatomical information image on nasopharyngea MSCT l examination with the carcinoma clinical and determine the best value reconstruction increment overlapping that can provide optimal anatomical information image on nasopharyngeal MSCT examination with the clinical of carcinoma.Methods: This research was quantitative research with pre-experimental approach with one shoot case study method. This research was carried out by means of SIEMENS